Prevalence of Newcastle Disease Virus in Commercial and Backyard Poultry in Haryana, India - Joshi, Vinay G.; Chaudhary, Deepika; Bansal, Nitish; Singh, Renu; Maan, Sushila; Mahajan, Nand K.; Ravishankar, Chintu; Sahoo, Niranjana; Mor, Sunil K.; Radzio-Basu, Jessica; Herzog, Catherine M.; Kapur, Vivek; et al. (Frontiers in Veterinary Science, 2021)
Newcastle disease virus (NDV) causes Newcastle disease (ND) in poultry. The ND is a highly contagious disease, which is endemic in several countries despite regular vaccination with live or killed vaccines. Studies on NDV in India are mostly targeted towards its detection and characterization from disease outbreaks. A surveillance study was undertaken to determine NDV prevalence throughout the state of Haryana from March 2018 to March 2020 using a stratified sampling scheme. The state was divided into three different zones and a total of 4,001 choanal swab samples were collected from backyard poultry, commercial broilers, and layers. These samples were tested for the M gene of NDV using real-time RT-PCR. Of the 4,001 samples tested, 392 were positive (9.8% apparent prevalence; 95% CI: 8.9-10.8%) for the M gene. Of these 392 M gene positive samples, 35 (8.9%; 95% CI: 6.4-12.3%) were found to be positive based on F gene RT-PCR. Circulation of NDV in commercial and backyard poultry highlights the importance of surveillance studies even in apparently healthy flocks. The information generated in this study should contribute to better understanding of NDV epidemiology in India and may help formulate appropriate disease control strategies for commercial and backyard birds.